Impact of Strategic Human Resource Management Practices on Business Competitive Priorities Mediated by Organizational Citizenship Behavior in Jordanian Manufacturing Companies (Global Journal of Management and Business Research, 2021)
Abstract not found
Keywords: recruitment and selection; compensations; training and development organizational citizenship behavior; quality; flexibility; delivery